ANALISIS NILAI TAMBAH PRODUK PERIKANAN LEMURU PELABUHAN MUNCAR BANYUWANGI - Ratna Purwaningsih (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2015)
Lemuru fisheries in Bali strait, Muncar, Banyuwangi has strategic role for fish canning industries. Sardinella lemuru has low economic value as fresh fish but high as fish canning. Fisheres production system must be viewed as a whole value added system, starting from landing site at fisheries port to fish processing industries and distributed to the consumers. Lemuru from Muncar fishery port are distributed to canning industries, cold storage, flour and fish oil industries. This research aims to (1) describe fish distribution pattern from landing site to industries, (2) determine fish processing cost in industries, (3) determine the economic added value of lemuru as various products. Data collection method are interview with fisher and industries, direct observation and secondary data from research report and scientific publication. Cost in fish processing industries is classified as investment cost, operating cost and overhead cost. The totalcost will becompared to the product price, from which the differenceis theadded value. Value-added creation also considers the conversion rate between fresh fish products into finished products. Research shows that, among the fish processing industries under consideration, canning industry has highest added value in the amount of USD 3.5 million/ton of finished product. For the canning industry, every 1 ton of fish can equal be converted to 1,5 ton of canned fish products. Flour and fish oil industry, in the meantime, generates added value of Rp 2.3million/ton. Finally, cold storage industry has lowest added value of 1.8 million/ton of product. Cold storage industry produces frozen fish and has a function for storing fish production in the harvest season.